The Addicted Narcissist: How Substance Addiction Contributes to Pathological Narcissism With Implications for Treatment - Laurence, Kim (Auckland University of Technology, 2016)
The narcissistic client is among the most difficult to treat, yet Narcissistic Personality Disorder is the least researched in the category in which it fits (Campbell, Miller, & Pilkonis, 2007). Narcissism, in general, is becoming a Western cultural phenomenon as individualism is becoming more encouraged over community values. The increased rate of substance dependency disorders runs parallel to the increased sense of grandiosity and entitlement in the 21st century (Twenge, 2006). Substance use among the general population is increasingly becoming a public health issue and is associated with many social, psychological and physiological costs that affect both addict and the people in their lives (Ham & Hope, 2003). This dissertation is a hermeneutic literature review, examining the relationship between pathological narcissism and addiction, and in particular, the narcissistic individual who enters into substance dependency. The research identified a number of themes in the literature, including personality as a predisposition to addiction, a connection with differential diagnoses, relevance of specific personality characteristics, substance use as self-medication, and disengagement with Alcoholics Anonymous. The research also identified significant gaps in currently available literature, including the examination of covert narcissism, and interpersonal relationships relevant to the addicted narcissist. In addition to summarising, exploring and discussing the themes of the literature, another aim was to consider the implications these findings have for the treatment of the client population.
Keywords: Narcissism; Addiction; Substance use; Narcissistic personality disorder; Mental health